Circuits of the sacred: a faggotology in the Black Latinx Caribbean - Decena, Carlos Ulises (Writing matters!, 2023)
"In Circuits of the Sacred Carlos Ulises Decena examines transnational Black Latinx Caribbean immigrant queer life and spirit. Decena models what he calls a faggotology-the erotic in the divine as found in the disreputable and the excessive-as foundations to queer Black critical and expressive praxis of the future. Drawing on theoretical analysis, memoir, creative writing, and ethnography of Santería/Lucumí in Santo Domingo, Havana, and New Jersey, Decena moves between languages, locations, pronouns, and genres to map the itineraries of Blackness as a "circuit," a multipronged and multisensorial field. A feminist pilgrimage and extended conversation with the dead, Decena's study is a provocative work that transforms the academic monograph into a gathering of stories, theoretical innovation, and expressive praxis to channel voices, ancestors, deities, theorists, artists, and spirits from the vantage point of radical feminism and queer of color thinking"--